International Monetary Fund Annual Report 2017 Financial Statements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
The audited consolidated financial statements of the International Monetary Fund as of April 30, 2017 and 2016 include the related consolidated statements of comprehensive income, of changes in reserves, resources, and retained earnings, and of cash flows for the years then ended. The IMF's financial statements were audited by external auditing firm PricewaterhouseCoopers, LLC, which certified that they were prepared and presented in accordance with International Financial Reporting Standards as issued by the International Accounting Standards Board. The standards include the design, implementation, and maintenance of internal control relevant to the preparation and fair presentation of consolidated financial statements that are free from material misstatement, whether due to fraud or error.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet